Investigation of the Dzyaloshinskii-Moriya interaction and room temperature skyrmions in W/CoFeB/MgO thin films and microwires - Jaiswal, Samridh; Litzius, Kai; Lemesh, Ivan; Buttner, F.; Finizio, Simone; Raabe, Jörg; Weigand, M.; Lee, Kyujoon; Langer, Juergen; Ocker, Berthold; Jakob, Gerhard; Beach, G. S. D.; et al. (Applied Physics Letters, 2017)
Recent studies have shown that material structures, which lack structural inversion symmetry and have high spin-orbit coupling can exhibit chiral magnetic textures and skyrmions which could be a key component for next generation storage devices. The Dzyaloshinskii-Moriya Interaction (DMI) that stabilizes skyrmions is an anti-symmetric exchange interaction favoring non-collinear orientation of neighboring spins. It has been shown that materials systems with high DMI can lead to very efficient domain wall and skyrmion motion by spin-orbit torques. To engineer such devices, it is important to quantify the DMI for a given material system. Here, we extract the DMI at the Heavy Metal/Ferromagnet interface using two complementary measurement schemes, namely, asymmetric domain wall motion and the magnetic stripe annihilation. By using the two different measurement schemes, we find for W(5 nm)/Co20Fe60B20(0.6 nm)/MgO(2 nm) the DMI to be 0.68 ± 0.05 mJ/m2 and 0.73 ± 0.5 mJ/m2, respectively. Furthermore, we show that this DMI stabilizes skyrmions at room temperature and that there is a strong dependence of the DMI on the relative composition of the CoFeB alloy. Finally, we optimize the layers and the interfaces using different growth conditions and demonstrate that a higher deposition rate leads to a more uniform film with reduced pinning and skyrmions that can be manipulated by spin orbit torques.
CRIS-Team Scopus Importer:2023-03-27